Internal sample process control improves cultivation-independent quantification of thermotolerant Campylobacter. (April 2019) - Pacholewicz, Ewa; Buhler, Christiane; Wulsten, Imke F.; Kraushaar, Britta; Luu, Huong Quynh; Iwobi, Azuka N.; Huber, Ingrid; Stingl, Kerstin
Abstract: Quantification of Campylobacter is challenging and one major reason is the fact that bacteria lose cultivability due to cold or oxygen stress during storage at retail. Alternative live/dead discriminatory qPCR currently lacks standardization and might overestimate live cells in the presence of dead cells. In this study an internal sample process control (ISPC) was developed. The ISPC consists of a specified number of peroxide-killed C. sputorum cells to be added to each sample in order to monitor (i) the level of reduction of the signal from dead cells and (ii) DNA losses during sample processing. A species-specific fragment of the 16S rRNA gene of C. sputorum was selected as real-time PCR target, based on its similar size and gene copy number compared to the C. jejuni / coli / lari target and confirmed in an exclusivity study. Extension of the amplification oligonucleotides for the target of thermotolerant Campylobacter improved real-time PCR efficiency, rendering the method suitable for quantification according to international standards. Concordant PCR signal variation of both C. jejuni and C. sputorum targets in co-inoculated chicken rinses verified the suitability of the ISPC. This provides a crucial step towards implementation of cultivation-independent quantification for improved food safety of fastidious bacteria. Highlights: We developed the first quantitative control for a food-borne pathogen applicable in live qPCR. qPCR efficiency was increased to match international standards. The ISPC is suitable for monitoring matrix and processing effects. Campylobacter as a fastidious organism serves as model to challenge CFU in food safety monitoring. We provide a crucial step towards implementation of cultivation-independent quantification.